Clinical and Spectral-Domain Optical Coherence Tomography Findings of Patients with Incomplete Visual Recovery after Anatomically Successful Retinal Detachment Surgery. (16th February 2015) - Tsilimbaris, Miltiadis K.; Chalkia, Aikaterini; Tsika, Chrysanthi; Anastasakis, Anastasios; Kontadakis, Georgios A.
Abstract : Purpose . To identify causes of incomplete visual recovery in patients with anatomically successful retinal detachment surgery. Methods . This was a retrospective study of 61 eyes of 61 patients with at least 12-month follow-up and complete preoperative, intraoperative, and postoperative record. Postoperative visual acuity (VA) more than 0.18 logMAR was considered as incomplete visual recovery. Complete ophthalmic examination and Spectral-Domain OCT (SD-OCT) imaging were performed at last follow-up. Results . Twenty-nine eyes (47.5%) had a postoperative VA < 0.18 logMAR and 32 eyes (52.5%) had a postoperative VA ≥ 0.18 logMAR. Mean follow-up was 32.8 ± 17.3 months. Incomplete visual recovery was strongly correlated with presence of macular pathology ( P = 0.002), a detached macula preoperatively ( P = 0.02), retinotomy ( P = 0.025), and pars plana vitrectomy and use of silicon oil as a tamponade agent ( P = 0.009). Also, although there was a strong correlation between ellipsoid zone disruption and incomplete visual recovery, a distinct, more course pathology could be identified in all cases of poor visual recovery related to edema, thickening, or atrophy of the macula. Conclusion . The careful postoperative evaluation of the macula using biomicroscopy and SD-OCT can help in diagnosis of alterations that can be associated with incomplete visual recovery.